Examining sports motivation : comparison between Singaporean and Japanese - Yoshida, Yukie (2017)
Cultural and social background influence the type of motivation people have in sports participation. This study aims to find out if there is any significant difference in sports motivation between Singaporean and Japanese. Self Determination Theory (SDT) was used as a framework of present study where the types of motivation are categorized as intrinsic, integrated, identified, introjected, external and amotivation. Sports Motivation Scale-II (SMS-II) was used to measure the type of motivation, and multivariate analysis of variance (MANOVA) was used to find out the differences between the two groups which consists of 349 Singaporean and 653 Japanese. It was hypothesized that Singaporean score higher for extrinsic motivation whereas Japanese score higher for intrinsic motivation. Result showed that there was a statistically significant difference between Singaporean and Japanese university student-athletes on the combined dependent variables (F = (6, 994) = 58.9, p = .000, partial eta squared = .262). Intrinsic, integrated, identified and introjected motivation were significantly different between the two groups where Japanese scored higher only for introjected motivation (F = (1, 92.385) = 62.292, p = .000, partial eta squared = .059). There were minimum motivation differences in relation to frequency of training and competition level between the two groups. Motivation may be indeed influenced by culture and social factors. Intrinsic motivation may not necessarily lead to higher level of sports performance. Future study may include the measurement of performance and finding out the optimal level of motivation related to ideal performance level.